Numerical simulation of elastic wave propagation in textile composite structures - Thierry, Victor (2020)
This manuscript presents a novel approach allowing damped ultrasonic wave propagation analysis of textile composite structures modelled at a mesoscopic level (i.e. modelling the yarns and matrix distinctively). Current modelling approaches rely on material homogenisation for analysis at a macroscopic scale and thus overlook the effect of textile architecture on wave propagation. This work aims at predicting wave propagation characteristics in damped textile composite structures and the induced complex phenomena for applications in structural health monitoring.